2009
DOI: 10.1128/jvi.02551-08
|View full text |Cite
|
Sign up to set email alerts
|

Role of Natural Killer Cells in a Cohort of Elite Suppressors: Low Frequency of the Protective KIR3DS1 Allele and Limited Inhibition of Human Immunodeficiency Virus Type 1 Replication In Vitro

Abstract: cells on viral replication in CD4؉ T lymphoblasts. Although we had postulated that NK cells of ES would be highly effective at controlling viral replication, we found that NK cells from some, but not all, ES were capable of inhibiting replication in the presence of interleukin-2, and the inhibition was less robust than that mediated by CD8 ؉ T cells. Additionally, we examined whether particular alleles of the KIR receptors, specifically KIR3DS1 and KIR3DL1, or allele-ligand combinations correlated with the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 38 publications
1
58
1
Order By: Relevance
“…+ NK cells in a HLA-Bw4 80I + target cell genetic background (15); however, this result has not been subsequently reproduced in vivo in EC/LTNP cohorts (16). Various combinations of these mechanisms seem to be involved in the successful control of HIV replication in some LTNP and EC patients; however, none of them taken alone can fully explain this condition, and it has not been shown to identify all of these patients.…”
Section: Nkp44ligandmentioning
confidence: 73%
“…+ NK cells in a HLA-Bw4 80I + target cell genetic background (15); however, this result has not been subsequently reproduced in vivo in EC/LTNP cohorts (16). Various combinations of these mechanisms seem to be involved in the successful control of HIV replication in some LTNP and EC patients; however, none of them taken alone can fully explain this condition, and it has not been shown to identify all of these patients.…”
Section: Nkp44ligandmentioning
confidence: 73%
“…NK cells from both viraemic and non-viraemic LTNPs have been shown to produce significantly higher levels of gamma interferon (IFN-c) than progressors and healthy uninfected subjects, which is the main mechanism by which NK cells mediate control of infection (O'Connor et al, 2007;Vieillard et al, 2010). NK cells are certainly important for controlling viral infection in HIV-infected subjects, albeit CD8 + T cells have been shown to exhibit superior control of HIV-1 replication in EC subjects (O'Connell et al, 2009).…”
Section: Innate Immunitymentioning
confidence: 99%
“…Phytohemagglutinin (PHA)-activated CD4 + T cells from ES are susceptible to infection (7,8,(26)(27)(28)(29)(30), but studies that have used CD3 stimulation to activate CD4 + T cells from ES have yielded conflicting results. One study suggested that cells from ES were resistant to infection because of selective up-regulation of cyclin-dependent kinase inhibitor p21 (31), whereas another study also found resistance of ES CD4 + T cells to HIV-1 infection but showed that p21 plays no role in this phenomenon (32).…”
mentioning
confidence: 99%